Argentinean immigrants in Spain: phonetic, morphological and lexical accommodation to the variety of Malaga - Von-Essen, María Clara (My University, 2018)
The aim of this project is to establish the sociolinguistic accommodation of an Argentinean-speaking community distinguishing between: a) young immigrants (n = 12), and b) adult Argentinean immigrants (n = 12) in the city of Malaga, Spain. We will compare the accommodation of these two groups in order to determine if there are differences that could be related to age, gender, time of residence in the city of Malaga, etc.
Inmigrantes argentinos en España: acomodación fonética, morfológica y léxica a la variedad de la ciudad de Málaga
Keywords: Lingüística - Congresos; Dialects in contact; Argentinean immigration; Acoustic analysis; Zero crossings